Interpretation of the results of the 8th grade exam in 2023 from the perspective of a district. The need for autonomy and independence of schools and teachers - Marek Piotrowski (Studia z Teorii Wychowania)
Reform creators, government and local government authorities often uncritically accept the results of external examinations as measures of the effectiveness of school teaching. The method of assessing the work of teachers and schools using exam results is often questioned not only by teachers themselves, but also by some academic educators, especially critical ones, who point to non-school causes of differences in achievement, e.g. related to the environment. The article presents the interpretation of the results of the 8th grade exam as dependent on an extracurricular parameter - the wealth of local communities. At the same time, it highlights the need to treat the school as an autonomous institution for which recommendations to improve the quality of work must take into account the status of the local environment. This approach is a continuation of the measurement of the level of school competences carried out in districts managed by local governments, taking into account family capital (in the form of parents' education).